ANALISIS DAN DESAIN APLIKASI PEMBELAJARAN METAMORFOSIS KUPU-KUPU BERBASIS AUGMENTED REALITY - Ningsih, Fitria; Rusdiana, Lili; Rudini (SINTECH (Science and Information Technology) Journal, 2019)
Augmented Reality is one of technology that combines virtual world objects with the real world that allows it to be applied to Android-based smartphones because its users have penetrated into the realm of children. The need for analysis and design before building applications that later can help facilitate teachers in learning by displaying 3D objects and animations that make Students more interested in paying attention to the material provided and becoming more active in participating in the learning process. The purpose of this study is to analyze and design learning applications for Butterfly metamorphosis using Augmented Reality as an alternative learning media. Methods of collecting data are literature, observation, and interviews. The results of this study are in the form of application design regarding the metamorphosis phase of Butterflies ranging from caterpillars, larvae, pupae, to cocoons.